Effect of dietary medium-chain fatty acids on nursery pig growth performance, fecal microbial composition, and mitigation properties against porcine epidemic diarrhea virus following storage. (23rd November 2019) - Gebhardt, Jordan T; Thomson, Katelyn A; Woodworth, Jason C; Dritz, Steve S; Tokach, Michael D; DeRouchey, Joel M; Goodband, Robert D; Jones, Cassandra K; Cochrane, Roger A; Niederwerder, Megan C; Fernando, Samodha; Abbas, Waseem; et al.
Abstract: An experiment was conducted to evaluate the effect of dietary medium-chain fatty acid (MCFA ) addition on nursery pig growth performance, fecal microbial composition, and mitigation of porcine epidemic diarrhea virus (PEDV ) following storage. A total of 360 pigs (DNA 400 × 200, Columbus, NE; initially 6.7 ± 0.07 kg) were randomized to pens (5 pigs per pen) on the day of weaning (approximately 20 d of age), allowed a 6-d acclimation, blocked by BW, and randomized to dietary treatment (9 pens per treatment). All MCFA (Sigma–Aldrich, St. Louis, MO) were guaranteed ≥98% purity, including hexanoic (C6:0), octanoic (C8:0), and decanoic (C10:0) acids. Treatment diets were formulated in 2 phases (7 to 11 and 11 to 23 kg BW) and formulated to meet or exceed NRC requirement estimates. Treatments ( n = 8) were a dose response including 0%, 0.25%, 0.5%, 1.0%, and 1.5% added MCFA blend (1:1:1 ratio C6:0, C8:0, and C10:0), as well as treatments with individual additions of 0.5% C6:0, C8:0, or C10:0. Fecal samples were collected from pigs fed control and 1.5% MCFA blend diets on days 0 and 14 and analyzed using 16s rDNA sequencing. Following feed manufacture, feed was stored in bags at barn temperature and humidity for 40 d before laboratory inoculation with PEDV. Subsamples of retained feed were inoculated with PEDV to achieve a titer of 10 4 TCID50 /g and separate sample bottles were analyzed on 0 and 3 d post-inoculation (dpi). Overall, ADG and ADFI were increased (linear, P ≤ 0.010) and feed efficiency (G:F) improved (linear, P = 0.004) with increasing MCFA blend. Pigs fed 0.5% C8:0 had greater ( P = 0.038) ADG compared with pigs fed the control diet, and G:F was improved ( P ≤ 0.024) when pigs were fed 0.5% C6:0, 0.5% C8:0, or 0.5% C10:0 compared with control. An inclusion level × day interaction was observed (quadratic, P = 0.023), where PEDV Ct values increased (quadratic, P = 0.001) on 0 dpi with increasing levels of MCFA blend inclusion and also increased on 3 dpi (linear, P < 0.001). Fecal microbial diversity and composition were similar between control and 1.5% MCFA blend. In summary, the use of MCFA in nursery pig diets improves growth performance, provides residual mitigation activity against PEDV, and does not significantly alter fecal microbial composition.